Loneliness, self-compassion, and psychological well-being among adults in Sarawak: Self-compassion as the mediator - Emilia Ting, Ing Chieh; Ting, Chuong Hock (Zes Rokman Resources, 2026)
Mental health concerns are on the rise in Malaysia, particularly depression, which has doubled in prevalence from 2019 to 2023, according to the National Health and Morbidity Survey 2023. Loneliness has emerged as a significant contributor to poor mental health outcomes, negatively impacting both physical and psychological well-being. This study explored the associations between loneliness, self-compassion, and psychological well-being among adults aged 18 to 64 in Sarawak, Malaysia, and examined whether self-compassion mediates the relationship between loneliness and psychological well-being. A total of 394 participants (M = 32.67, SD = 11.07) were recruited using snowball sampling. Participants completed validated instruments, including the UCLA Loneliness Scale (Version 3), the Self-Compassion Scale (SCS), and the Scale of Psychological Well-Being (SPWB). Results showed that participants reported moderate levels of loneliness, self-compassion, and psychological well-being. Loneliness was significantly negatively correlated with both self-compassion (r = -.560, p < .001) and psychological well-being (r = -.508, p < .001), whereas self-compassion was positively correlated with psychological well-being (r = .629, p < .001). Mediation analysis revealed that self-compassion partially mediated the impact of loneliness on psychological well-being (Effect = −0.7855, 95% CI [−1.0248, −0.5732]). This study contributes to the literature by examining the relationships between loneliness, self-compassion, and psychological well-being within the Malaysian context, focusing on adults in Sarawak. These findings underscore the protective role of self-compassion and support its integration into culturally relevant mental health interventions.